Therapeutic Nutritional Knowledge regarding Cardio-Vascular Diseases among Nursing Students - Prakash, Satyam; Yadav, Khushbu (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: The accountability of nurses for nutritional care and best nutritional practices in nutritional management has been shown to improve patient outcomes at hospitals. Several studies had been conducted before to explore the level of nutritional knowledge among nurses in different countries but there is paucity of data among nursing students. Therefore, the present study was designed to focus on bachelor level nursing students about the therapeutic nutritional towards CVDs Material and Methods: A cross sectional descriptive study was conducted among 97 nursing students studying in B.Sc. nursing and PBBN programme. Random sampling technique was used. Structured questionnaire was distributed to each participant to choose the most correct answer. The collected data was entered in Microsoft Excel for analysis. The level of knowledge was assessed on the basis of percentage score. Results: Out of total students, 42% were less than or equal to 20 years and 58% were greater than 20 years. Most of the students were from Dhanusha district. Almost all respondents had heard about the different types of diet, CVD (98.96%) but 1.03% respondent was not familiar with CVD. 93.81% respondents knew high blood cholesterol increases the incidence of heart disease and 85.56% responded that caffeinated beverage is harmful for myocardial infarction. The poor knowledge was found about good fats and bad fats among respondents. Conclusion: The basic information regarding CVDs was significant but the therapeutic nutritional knowledge among the nursing students was found to be satisfactory. Therefore, the improvement in the curriculum of undergraduate nursing courses is necessary regarding the proper therapeutic nutritional knowledge for its integration into health services effectively at hospitals. Janaki Medical College Journal of Medical Sciences (2016) Vol. 4 (2): 24-32